ГӘПТИҢ АКТУАЛЬ БӨЛИНИЎИНДЕ ЖАНАПАЙЛАРДЫҢ ХЫЗМЕТИ - Нзанова, С.К. (SCIENCE and SOCIETY, 2021)
Particles in a sentence perform semantic, syntactic, stylistic, communicative and pragmatic functions. A speaker using particles, not just expressing his/her opinion, increases the expressiveness of the utterance, loading a wide range of pragmatic meanings, such as his/her emotions and desires. The article examines the role of the particles of the Karakalpak language in the actual division of the sentence.
Keywords: particles; communicative structure of a sentence; actualizer; theme; rheme; communicative center